2023
DOI: 10.3390/ph16050641
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Antiviral Activities of Glycyrrhizic Acid, Glycyrrhetinic Acid and Glycyrrhetinic Acid Monoglucuronide

Abstract: Licorice, a natural medicine derived from the roots and rhizomes of Glycyrrhiza species, possesses a wide range of therapeutic applications, including antiviral properties. Glycyrrhizic acid (GL) and glycyrrhetinic acid (GA) are the most important active ingredients in licorice. Glycyrrhetinic acid 3-O-mono-β-d-glucuronide (GAMG) is the active metabolite of GL. GL and its metabolites have a wide range of antiviral activities against viruses, such as, the hepatitis virus, herpes virus and severe acute respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 156 publications
0
9
0
Order By: Relevance
“…GL is metabolized to GA under the action of gut bacteria. In addition, GL is metabolized in the intestine or be transformed via enzymolysis to GA-3-O-mono-β-d-glucuronide (GAMG), a distal glucuronic acid hydrolysate of GL with higher bioavailability and stronger physiological functions ( Zuo et al, 2023 ).…”
Section: Glycyrrhizic Acidmentioning
confidence: 99%
“…GL is metabolized to GA under the action of gut bacteria. In addition, GL is metabolized in the intestine or be transformed via enzymolysis to GA-3-O-mono-β-d-glucuronide (GAMG), a distal glucuronic acid hydrolysate of GL with higher bioavailability and stronger physiological functions ( Zuo et al, 2023 ).…”
Section: Glycyrrhizic Acidmentioning
confidence: 99%
“…Besides, phytochemicals from Yashtimadhu and Vasaka demonstrate good binding energies against M pro and RdRp protein targets of the virus. It also Other active pharmacological properties against the virus such as inhibiting viral entry and replication [ [15] , [16] , [17] ].…”
Section: Discussionmentioning
confidence: 99%
“…Other in-silico studies demonstrate that phytochemicals present in herbs used regularly as a part of Indian diet, like Bilwa , Khus ( Vetiveria zizanioides ), Drumstick ( Moringa oleifera ), and Pomegranate ( Punica granatum ) exhibit significant binding with RdRp and M pro proteins of SARS-CoV-2 virus [ 14 ]. Components of Yashtimadhu ( Glycyrrhiza glabra ), another well-known ayurvedic herb, were noticed to have a significant binding affinity with various SARS-CoV-2 proteins (main protease, spike protein, and RdRp protein) and host macromolecular targets such as human (ACE2 and furin) proteins [ 15 ]. Vasaka ( Adhatoda vasica ), another potent ayurvedic compound, exhibited strong binding energy with M pro of SARS-CoV-2 (−114.9 kcal/mol) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous in vitro and in vivo studies suggest that Gly is a broad-spectrum antiviral against different viruses affecting both humans and animals. Among the viruses affecting humans for which Gly's antiviral action has been observed are, in addition to human papillomavirus (HPV), herpesviruses (HSV-1, HSV-2, VZV, EBV, KSHV), hepatitis viruses (HBV, HCV), influenza viruses, human immunodeficiency virus (HIV), coronaviruses (SARS-CoV, SARS-CoV-2), rotavirus, coxsackievirus or Zika [4,6,7].…”
Section: Antiviral Activity Of Glycyrrhizinic Acidmentioning
confidence: 99%
“…Other mechanisms of antiviral action have been described for Gly against other viruses, and it has not been ruled out that some of these may also be involved in its action against HPV infectious processes. It has been observed that Gly can be effective since the steps prior to infection, directly inactivating the viruses or preventing their binding and entry into the host cell, until the infection is established by inhibiting viral replication, stimulating apoptosis, or even modulating the immune response [4,6,7]. Specifically, it has been observed that Gly can directly inactivate HSV-1 and VZV viruses [11][12][13].…”
Section: Antiviral Activity Of Glycyrrhizinic Acidmentioning
confidence: 99%